2016
DOI: 10.1038/onc.2016.369
|View full text |Cite
|
Sign up to set email alerts
|

Myoferlin regulates cellular lipid metabolism and promotes metastases in triple-negative breast cancer

Abstract: Myoferlin is a multiple C2-domain-containing protein that regulates membrane repair, tyrosine kinase receptor function and endocytosis in myoblasts and endothelial cells. Recently it has been reported as overexpressed in several cancers and shown to contribute to proliferation, migration and invasion of cancer cells. We have previously demonstrated that myoferlin regulates epidermal growth factor receptor activity in breast cancer. In the current study, we report a consistent overexpression of myoferlin in tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
69
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 45 publications
9
69
0
Order By: Relevance
“…In the same line, our group has identified myoferlin, a novel exosomal protein, as a potential prognostic marker in breast cancer and pancreatic cancer [111][112][113][114]. We have demonstrated that overexpression of myoferlin in triple negative breast cancer (TNBC) is a negative prognostic factor associated with worse overall survival (OS) and metastatic disease [112]. Our findings in pancreatic cancer also reveal a correlation between myoferlin overexpression and a poor clinical outcome [114].…”
Section: Exosomal Biomarkerssupporting
confidence: 58%
See 1 more Smart Citation
“…In the same line, our group has identified myoferlin, a novel exosomal protein, as a potential prognostic marker in breast cancer and pancreatic cancer [111][112][113][114]. We have demonstrated that overexpression of myoferlin in triple negative breast cancer (TNBC) is a negative prognostic factor associated with worse overall survival (OS) and metastatic disease [112]. Our findings in pancreatic cancer also reveal a correlation between myoferlin overexpression and a poor clinical outcome [114].…”
Section: Exosomal Biomarkerssupporting
confidence: 58%
“…Investigators have demonstrated that CD63+ exosomes are present at a higher level in malignant cells compared to normal cells [107,110]. In the same line, our group has identified myoferlin, a novel exosomal protein, as a potential prognostic marker in breast cancer and pancreatic cancer [111][112][113][114]. We have demonstrated that overexpression of myoferlin in triple negative breast cancer (TNBC) is a negative prognostic factor associated with worse overall survival (OS) and metastatic disease [112].…”
Section: Exosomal Biomarkersmentioning
confidence: 82%
“…Our ongoing studies will explore the consequence of myoferlin over-expression on MAPK/ERK signalling pathways in a transgenic mouse model, to better elucidate the functional consequences of myoferlin cleavage and its potential relationship to growth factor receptor signalling and the metastatic properties of cancer cells. Enzymatic cleavage of myoferlin may explain detection of myoferlin as a 240/170 kDa N-terminal doublet band in tumour samples and cancer cell lines in recent reports describing a role for myoferlin in tumorigenesis and cancer cell metastasis [16,2830], potentially illuminating a functional adaptation of myoferlin relevant to cellular signalling and oncogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Our interest in myoferlin was piqued by reports showing myoferlin as a doublet band in western blots when detected with N-terminal epitope specific antibodies [16,2830]. This was reminiscent of the N-terminal calpain-cleavage fragment we reported for dysferlin [26,27].…”
Section: Introductionmentioning
confidence: 90%
“…VM v 2 P value Yes (14) No ( results, the expression of MMP-2 decreased more than 40% in MYOF down-regulated cells (Fig. 3C), which correlates with the decreased mRNA levels detected by RT-PCR (Fig.…”
Section: Variables Casesmentioning
confidence: 56%